New Macrostylidae Hansen, 1916 (Crustacea: Isopoda) from the Gay Head-Bermuda transect with special consideration of sexual dimorphism - Riehl, Torben; Wilson, George D. F.; Hessler, Robert R. (Zootaxa, 2012)
In the Asellota, sexual dimorphism is often characterized by males that show pronounced morphological differences after thefinal moult compared to females but also to sub-adult males. Such a sexual dimorphism may strongly complicate allocation ofthese terminal males to conspecifics. Consequently, we regard it to be a likely explanation for why in 50% of the described spe-cies of the family Macrostylidae Hansen, 1916, only one sex is known. Based on detailed description of two previouslyunknown species of the isopod genus Macrostylis Sars, 1864, the changes in the morphology that can occur during the finalmoult of the males are highlighted. M. dorsaetosa n. sp. is unlike any other species owing to the row of spine-like setae on theposterior margins of pereonites 5–6. M. strigosa Mezhov, 1999 shows remarkable similarity but lacks these setae. In M. papil-lata n. sp., cuticular ridges overlap posteriorly with the margin of the pereonites 1–4 and head forming a warty appearance. Thisspecies is easily identifiable and unlike any previously described macrostylid owing to the presence of the tergal articulationbetween pleonite 1 and pleotelson. Information for the identification of terminal males is provided and implications of our results for future taxonomic and systematic work on this isopod family are discussed.